2020
DOI: 10.1096/fba.2020-00008
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐ORAI1 antibody DS‐2741a, a specific CRAC channel blocker, shows ideal therapeutic profiles for allergic disease via suppression of aberrant T‐cell and mast cell activation

Abstract: ORAI1 constitutes the pore‐forming subunit of the calcium release‐activated calcium (CRAC) channel, which is responsible for store‐operated calcium entry into lymphocytes. It is known that ORAI1 is essential for the activation of T cells and mast cells and is considered to be a potent therapeutic target for autoimmune and allergic diseases. Here, we obtained a new humanized antibody, DS‐2741a, that inhibits ORAI1 function. DS‐2741a bound to human‐ORAI1 with high affinity and without cross‐reactivity to rodent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…This is evidenced by phenotype observations in patients or animal models with abnormal ORAI1 or STIM1 expression, which shows compromised CD4+ and CD8+ T cell functions related with humoral and cellular immunity, ultimately leading to immunodeficiencies and susceptibility to severe infections [19,22]. Considering that inflammation and autoimmune diseases are related with abnormal immune reactions, a CRAC channel inhibitor could be used to get rid of related diseases without causing severe side effects [23][24][25]. In our data, we showed that the CRAC current was successfully inhibited by treating nootkatone using patch clamp analysis (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by phenotype observations in patients or animal models with abnormal ORAI1 or STIM1 expression, which shows compromised CD4+ and CD8+ T cell functions related with humoral and cellular immunity, ultimately leading to immunodeficiencies and susceptibility to severe infections [19,22]. Considering that inflammation and autoimmune diseases are related with abnormal immune reactions, a CRAC channel inhibitor could be used to get rid of related diseases without causing severe side effects [23][24][25]. In our data, we showed that the CRAC current was successfully inhibited by treating nootkatone using patch clamp analysis (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function changes in ORAI1 or its activator STIM1 inhibit CRAC currents and SOCE [10,[16][17][18]. A previous report has illustrated the important role of ORAI1 in allergic skin disorders [19], and more recently, DS-2741a, an anti-ORAI1 antibody, has been shown to suppress T cell and mast cell functions [20]. In addition, although allergic responses can now be effectively medicated, there are still misgivings concerning the adverse side effects of antiallergic drugs and the associated increased medical expenses.…”
Section: Original Articlementioning
confidence: 96%
“…The inhibition of other ion channels being a major concern [ 54 ]. These inhibitors do not appear to be superior to medications such as ciclosporin A. Functional antibodies against human CRAC, have been developed and characterized for the neutralization of Ca2+ entry via CRAC channels [ 55 , 56 ]. Anti-Orai1 antibodies in vitro has been show inhibition of T cell proliferation and cytokine production in mouse model of graft-versus-host disease (GVHD) [ 57 ].…”
Section: Immunologycal Impact Of Orai1 and Kv13 Channels Inhibitionmentioning
confidence: 99%